SGRP Annual Report 2006: Of the CGIAR System-wide Genetic Resources Programme - CGIAR Systemwide Genetic Resources Programme (2007)
The System-wide Genetic Resources Programme (SGRP) unites all of the independent centres of the Consultative Group on International Agricultural Research (CGIAR) in a collaborative effort to sustain biodiversity for current and future generations. The diversity of plant, animal, forest and aquatic genetic resources supplies the building blocks for sustainable agriculture. SGRP harnesses the expertise and experience of the centres and their partners to put this diversity to work in fighting poverty, bringing health and food security, and protecting the environment. SGRP provides the CGIAR with a flexible means of working in the genetic resources arena, serving as an umbrella and communication mechanism to optimize, bring cohesiveness, and add value to the wide range of genetic resources activities pursued by the CGIAR centres. Through SGRP, centres share information and knowledge, conduct joint research, establish common policies and practices, stay abreast of developments in the global genetic resources sphere, and contribute to international debate.